A Fragilidade ambiental como suporte na identificação de conflitos ambientais na APA da Marituba do Peixe, Alagoas - Oliveira, Alex Nazário Silva (2017)
Conservation units represent an important strategy in the conservation of natural resources, being considered a powerful tool for the construction of conservation policies and for sustainability regarding the use of natural resources. However, increasing anthropogenic interventions, acting upon the environment, indiscriminately interfering in areas that are considered environmentally fragile, have been modifying their elements and processes, altering their natural dynamics and entailing in several negative impacts. As such, this research aimed at identifying and analyzing the conflicts between the areas with different levels of environmental vulnerability within the “Área de Proteção Ambiental (APA) da Marituba do Peixe”¹ and its Environmental Zoning, and also conducting comparisons and contrasts of all information by using geo-processing techniques. For such, an update of the geo-referenced database of the aforementioned Conservation Unit was carried out from digital thematic maps, topographic maps, aerial photographs, satellite images as well as field surveys which enabled the generation of the geo-environmental database in a 1: 25.000 scale and 5m spatial resolution. From the systemic theoretical basis, which served as support for the methodology of Jurandyr Ross (1994), the geo-environmental database was submitted to procedures of integration of information by means of geo-processing techniques, making use of QGIS software, licensed by GNU - General Public License, owned by Open Source Geospatial Foundation (OSGeo). The results show an environment with a tendency towards High Vulnerability, intensified by the indiscriminate use of vulnerable areas, which are susceptible to negative impacts due to soil degradation and fragmentation of native ecosystems of great importance. APA’s environmental conflict map, produced through comparisons and contrasts between emerging environmental vulnerability and the zoning in effect, presents a Conservation Unit with the following predominant percentages on its area: 37% of its area having Low Conflict, 33% in High Conflicts and 30% having No-Conflicts. Such percentages can be considered worrisome for the management of the Conservation Unit, which uses the Environmental Zoning in effect as a reference aiming at effectively fulfilling the objectives created, and which may present the commitment explicit in its guidelines as a direct reflex on the ecosystems. Therefore, a Geo-environmental Zoning proposal was developed based on the information found on the Maps of Vulnerability, Conflict and Urban Proximity Sites and Roads, contributing, then, for the protection and environmental conservation of the well-known “Pantanal Alagoano”².